2014
DOI: 10.1093/aje/kwu209
|View full text |Cite
|
Sign up to set email alerts
|

Serial Intervals of Respiratory Infectious Diseases: A Systematic Review and Analysis

Abstract: The serial interval of an infectious disease represents the duration between symptom onset of a primary case and symptom onset of its secondary cases. A good evidence base for such values is essential, because they allow investigators to identify epidemiologic links between cases and serve as an important parameter in epidemic transmission models used to design infection control strategies. We reviewed the literature for available data sets containing serial intervals and for reported values of serial interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
171
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 178 publications
(183 citation statements)
references
References 58 publications
9
171
0
3
Order By: Relevance
“…The reproduction ratio without vaccination is equal to ρ(Bγ) = 2.1. The parameter values for both the generation interval and the reproduction ratio are in line with other studies in literature (Boëlle, Ansart, Cori, & Valleron, 2011;Vink, Bootsma, & Wallinga, 2014).…”
Section: Case Descriptionsupporting
confidence: 89%
“…The reproduction ratio without vaccination is equal to ρ(Bγ) = 2.1. The parameter values for both the generation interval and the reproduction ratio are in line with other studies in literature (Boëlle, Ansart, Cori, & Valleron, 2011;Vink, Bootsma, & Wallinga, 2014).…”
Section: Case Descriptionsupporting
confidence: 89%
“…Mean serial intervals of Flu A-H3, Flu A-H1pdm09, and RSV and the duration between the onset of symptoms in a primary case and in its secondary cases are significantly shorter than in other contagious diseases, such as measles, varicella, smallpox, mumps, rubella, and pertussis [15]. Rapid diagnosis of a respiratory viral infection could reduce the rate of antibiotics use and unnecessary tests [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Kretzschmar et al found that the R 0 for pertussis across five European countries (Finland, Germany, Italy, The Netherlands, and the United Kingdom) during the 1990s was approximately 5.5, which is lower than R 0 estimates in previous studies (267). Moreover, in a recent systematic review, it was estimated that the mean interval from symptom onset in a primary pertussis case to symptom onset in a secondary case is 22.8 days (268). Similarly, the secondary attack rate is estimated to be at least 80% (171,269,270).…”
Section: Transmission Dynamics Of Pertussismentioning
confidence: 92%